2003
DOI: 10.1038/sj.bjc.6601162
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between 5-fluorouracil metabolism and treatment response in two variants of C26 murine colon carcinoma

Abstract: Following an i.p. dose of 150 mg kg À1 5-fluorouracil (5-FU), drug uptake and metabolism over a 2-h period were studied by in vivo 19 F magnetic resonance spectroscopy (MRS) for the murine colon carcinoma lines C26-B (5-FU-insensitive; n ¼ 11) and C26-10 (5-FUsensitive; n ¼ 15) implanted s.c. in Balb/C mice. Time courses for tumour growth, intracellular levels of FdUMP, thymidylate synthase (TS) activity, and 5-FU in RNA were also determined, and the effects of a 9.5-min period of carbogen breathing, starting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 35 publications
3
17
0
Order By: Relevance
“…Tumour uptake of [ 125 I]ICEU reached a stable maximal value of 3.370.3% ID g À1 . To our knowledge, this level of drug accumulation in the tumour appears higher than that of 5-Fu accumulation, that is the current 'gold standard' drug for the first-line of colorectal cancer treatment, reported in the same CT-26 tumour-bearing mice model (Kamm et al, 2003). These data appeared to us of particular interest since they supported our previous findings demonstrating that 40 mmol kg À1 of ICEU administered i.p.…”
Section: Discussionsupporting
confidence: 80%
“…Tumour uptake of [ 125 I]ICEU reached a stable maximal value of 3.370.3% ID g À1 . To our knowledge, this level of drug accumulation in the tumour appears higher than that of 5-Fu accumulation, that is the current 'gold standard' drug for the first-line of colorectal cancer treatment, reported in the same CT-26 tumour-bearing mice model (Kamm et al, 2003). These data appeared to us of particular interest since they supported our previous findings demonstrating that 40 mmol kg À1 of ICEU administered i.p.…”
Section: Discussionsupporting
confidence: 80%
“…It was hypothesized that for this tumor type, FU uptake was not a rate-limiting process for growth inhibition, possibly due to the relatively small size and well-perfused condition of the tumors. In C26B and C26-10 tumors in BalbC mice, there was no effect of carbogen breathing on FU uptake or anabolite production; however, carbogen + FU significantly inhibited tumor growth in C26-10 tumors [90]. The reason for the prolonged growth delay in C26-10 remained unclear in this study.…”
Section: Modulation Of Fu Uptake and Retentionmentioning
confidence: 90%
“…However, carbogen had no significant effect on 5FU uptake and metabolism in small RIF-1 tumours (0.8-1.6 g or 2.5-5% body-weight). These observations suggest the effects of carbogen on tumours may not be universal, and indeed different research groups using different tumour models have observed no change as well as both implied and real increases and decreases in tumour oxygenation, blood flow, pH and energy status [1,6,8,12,14,15,28,39]. We decided therefore to investigate the effects of carbogen on the pharmacokinetics of 5FU in two additional rodent tumour models, which have shown significant physiological responses to carbogen [29,35].…”
Section: Discussionmentioning
confidence: 99%